Genetic inhibition of glutamate allosteric potentiation of GABAARs in mice results in hyperexcitability, leading to neurobehavioral abnormalities - Yehong Du; Junjie Li; Maoju Wang; Qiuyun Tian; Yayan Pang; Ya Wen; Dongchuan Wu; Yu Tian Wang; Zhifang Dong (MedComm, 2023)
Abstract The imbalance between neuronal excitation and inhibition (E/I) in neural circuit has been considered to be at the root of numerous brain disorders. We recently reported a novel feedback crosstalk between the excitatory neurotransmitter glutamate and inhibitory γ‐aminobutyric acid type A receptor (GABAAR)‐glutamate allosteric potentiation of GABAAR functions through a direct binding of glutamate to the GABAAR itself. Here, we investigated the physiological significance and pathological implications of this cross‐talk by generating the β3E182G knock‐in (KI) mice. We found that β3E182G KI, while had little effect on basal GABAAR‐mediated synaptic transmission, significantly reduced glutamate potentiation of GABAAR‐mediated responses. These KI mice displayed lower thresholds for noxious stimuli, higher susceptibility to seizures and enhanced hippocampus‐related learning and memory. Additionally, the KI mice exhibited impaired social interactions and decreased anxiety‐like behaviors. Importantly, hippocampal overexpression of wild‐type β3‐containing GABAARs was sufficient to rescue the deficits of glutamate potentiation of GABAAR‐mediated responses, hippocampus‐related behavioral abnormalities of increased epileptic susceptibility, and impaired social interactions. Our data indicate that the novel crosstalk among excitatory glutamate and inhibitory GABAAR functions as a homeostatic mechanism in fine‐tuning neuronal E/I balance, thereby playing an essential role in ensuring normal brain functioning.